2021
DOI: 10.1021/acs.orglett.1c03052
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Carbene Coupling Reactions of Cyclobutanone N-Sulfonylhydrazones

Abstract: Described herein are the palladium-catalyzed cross-coupling reactions of cyclobutanone-derived N-sulfonylhydrazones with aryl or benzyl halides, suggesting that the metal carbene process and β-hydride elimination can smoothly occur in strained ring systems. Structurally diversified products including cyclobutenes, methylenecyclobutanes, and conjugated dienes are selectively afforded in good to excellent yields. Preliminary success in asymmetric carbene coupling reactions in strained ring systems has been achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…High-resolution mass spectral analysis (HRMS) data were measured on a Bruker Apex II. Substrates 1a – 1n and 2a – 2i were synthesized as per the previous literature.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution mass spectral analysis (HRMS) data were measured on a Bruker Apex II. Substrates 1a – 1n and 2a – 2i were synthesized as per the previous literature.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…On the other hand, N -tosylhydrazones were exploited as good coupling partners in palladium-catalyzed carbene coupling reactions and made an important breakthrough; , four-membered ring ketone-derived N -tosylhydrazones with strained were less explored until now. Only one example is the palladium-catalyzed coupling of cyclobutanone-derived N -tosylhydrazones with aryl or benzyl halides, which was discovered by Xia and co-workers . Therefore, developing more new types of reactions for the application of cyclobutanone N -tosylhydrazones is continuously in demand.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Xia and colleagues recently reported an elegant palladium-catalyzed cross-coupling reaction of benzyl chloride with strained cyclobutanone-derived Nsulfonylhydrazones, in which they found that N-triftosylhydrazone resulted in a much higher yield than N-tosylhydrazone (e.g., compound 70a, 84% vs 29% yield, respectively) (Scheme 15). 51 In addition, the reaction could be carried out in a one-pot procedure without the isolation and purification of Ntriftosylhydrazones. preparing, and investigating new types of functionalized Ntriftosylhydrazones; and (iii) applying these methods as key steps to improve the synthesis efficiency of drugs and natural products.…”
Section: Cross-coupling Of Benzyl Chlorides Withmentioning
confidence: 99%
“…6 In 2021, our group reported the synthesis of cyclobutenes and methylenecyclobutanes through palladium-catalyzed carbene coupling reactions of cyclobutanone-derived N-sulfonylhydrazones with organohalides. 7 On the basis of this study, we speculated that the strained cyclic π-allylpalladium intermediate could be generated from cyclobutenone-derived Ntosylhydrazones and organohalides via a carbene strategy, 8 thus providing an alternative avenue for the investigation of this intriguing intermediate. Herein, we carry out considerable exploration of this reaction and present our findings in this direction.…”
mentioning
confidence: 96%
“…On the contrary, transition metal-catalyzed carbene coupling reactions have attracted considerable attention in recent years . In 2021, our group reported the synthesis of cyclobutenes and methylenecyclobutanes through palladium-catalyzed carbene coupling reactions of cyclobutanone-derived N -sulfonylhydrazones with organohalides . On the basis of this study, we speculated that the strained cyclic π-allylpalladium intermediate could be generated from cyclobutenone-derived N -tosylhydrazones and organohalides via a carbene strategy, thus providing an alternative avenue for the investigation of this intriguing intermediate.…”
mentioning
confidence: 99%